Marginal Europeans in Colonial India : 1860-1920 - De, Sarmistha 1966- (Kolkata : Thema, 2008)
With reference to Bombay and Calcutta Presidencies of British India
Originally presented as the author's thesis (doctoral) -- Jadavpur University.
Library has 2 copies
Bibliography: p.268 - 275
Keywords: Europeans -- Bombay Presidency; Europeans -- India -- Bengal